Interleukin 13 (IL‐13) alters hypoxia‐associated genes and upregulates CD73. Issue 9 (16th July 2020) - Khalil, Syed Muaz; Bernstein, Isaac; Kulaga, Heather; Gour, Naina; Rowan, Nicholas; Lajoie, Stephane; Lane, Andrew P.
Abstract : Background: Interleukin 13 (IL‐13) is a pleiotropic cytokine that has been shown to be important in the pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP) and other type 2 inflammation–related diseases. Increased IL‐13 expression can elicit several pro‐inflammatory effects, including eosinophilia, and pathology such as increased mucus secretion. Polypogenesis in chronic rhinosinusitis (CRS) can be caused by hypoxia, which can also lead to hyperpermeability of airway epithelium and epithelium‐to‐mesenchymal translation through the upregulation of hypoxia‐associated genes, such as HIF1. Whether T‐helper 2 (Th2) inflammatory cytokines, such as IL‐13, can also induce sinonasal epithelial hypoxia‐associated genes is currently unknown. Methods: Human air‐liquid interface (ALI) sinonasal epithelial cell cultures treated with recombinant IL‐13 were analyzed by real‐time polymerase chain reaction (PCR) and flow cytometry to determine the effect on epithelial cells. Results: Whole tissue from CRSwNP subjects showed increased HIF1A gene expression. Treatment of fully differentiated human ALI cultures with IL‐13 resulted in a concurrent increase in HIF1A and ARNT messenger RNA (mRNA) expression. However, the level of EPAS1 expression was significantly reduced. IL‐13 also had a dose‐dependent response on the expression of HIF genes and the time course experiment showed peak expression of HIF1A and ARNT at 5 to 7 days poststimulation. Remarkably, CD73 surface expression also peaked at day 5 poststimulation. Conclusion: Our data suggests that IL‐13 can induce hypoxia signaling pathway genes leading to surface expression of CD73, which has an anti‐inflammatory effect.